Validation of Menstrual Disorders Questionnaire (MDQ) among medical students in Universiti Sains Malaysia - Lin, Yee Siau (Universiti Sains Malaysia, 2011)
The aim of this study was to determine the validity and reliability of knowledge and attitude on Menstrual Disorders Questionnaire (MDQ) among Year four medical students. A cross sectional study was undertaken at the School of Medical Sciences, Universiti Sains Malaysia. It started in July 2010 and ended in December 2010 using the structured self-administered questionnaire developed by a group of experts from Departments of Obstetrics and Gynaecology, Family Medicine, Epidemiology and Biostatistics. The questionnaire comprised 62 items in knowledge domain and 14 items in attitude domain related to menstrual disorders. A sample of 202 year four medical students was drawn for the data collection purpose in this study. There were 118 Malay respondents (58.4%) that consists 121 female (59.9%) and 81 male (40.1%). To assess the test-retest reliability, 98 students were drawn from all the respondents were given the same questionnaire for the second time after two weeks interval. The total of 24 items were removed for knowledge domain from the original questionnaire due to low correlations, too low or too high difficulty index, single item in one factor or low factor loading value. There were four items removed for the attitude domain from the original questionnaire due to the repetition of content. The mean score of items in MDQ ranged from 1.37 to 4.26. The factor loading value using Principal Component Analysis (PCA) extraction and Varimax rotation for both the knowledge and attitude domain ranged from 0.48 to 0.94. There were six sub-domains in knowledge domain and three sub-domains in attitude domain. Internal consistency of MDQ using Cronbach’s alpha ranged from 0.22 to 0.94. Test-retest reliability using intraclass correlation coefficient (ICC) was 0.74 for knowledge domain and 0.80 for attitude domain. Graphical presentation of test-retest reliability using Bland Altman plot showed the data distributed evenly in the plot. The MDQ had 0.5% ceiling effect at attitude domain and zero floor effect. The MDQ was valid and reliable to determine the attitude among medical students or the future health care personnel. It was valid but less reliable for measuring knowledge on menstrual disorders in this study. Further improvement of the questionnaire is needed to improve the reliability of the questionnaire.